Evaluación del efecto de las variables de formulación y de proceso sobre el comportamiento reológico y propiedades físicas partiendo de microemulsiones de silicona Industrias Químicas Saint Germain Ltda. (2019)
In the present project an evaluation of the formulation and process variables was carried out for the company Industrias Químicas Saint Germain Ltda., According to the main raw materials that make up a multicomponent system of emulsification. This system is composed of water, surfactant and silicone, with a series of variables that compromise the formation and stability such as concentration, speed and time. For the execution of this project, initially, a thorough investigation of the main components that make up a microemulsion was carried out; Then, according to the requirements that these components had to fulfill, the Colombian market was explored to acquire each raw material. Then, once the components were selected, the experimental development was carried out at the laboratory level, in order to analyze the rheological behavior, drop size, turbidity and stability that the final product gives. Once the final product was analyzed, the cost of obtaining the microemulsion was defined in order to reach an application use in the medium or long term. Given the above process steps, suitable manufacturing parameters and compositions were found for a microemulsion taking into account its optimum stability achieved. Once the procedure has been carried out, the proposed objectives are examined and it is defined what characterizes and what rheological behavior manifests the product obtained for a possible application in the medium or long term.